Meta-transcriptome Profiling of the Human-Leishmania braziliensis Cutaneous Lesion. - Stephen M Christensen; Laura A L Dillon; Lucas P Carvalho; Sara Passos; Fernanda O Novais; V Keith Hughitt; Daniel P Beiting; Edgar M Carvalho; Phillip Scott; Najib M El-Sayed; David M Mosser (Public Library of Science (PLoS), 2016)
Host and parasite gene expression in skin biopsies from Leishmania braziliensis-infected patients were simultaneously analyzed using high throughput RNA-sequencing. Biopsies were taken from 8 patients with early cutaneous leishmaniasis and 17 patients with late cutaneous leishmaniasis. Although parasite DNA was found in all patient lesions at the time of biopsy, the patients could be stratified into two groups: one lacking detectable parasite transcripts (PTNeg) in lesions, and another in which parasite transcripts were readily detected (PTPos). These groups exhibited substantial differences in host responses to infection. PTPos biopsies contained an unexpected increase in B lymphocyte-specific and immunoglobulin transcripts in the lesions, and an upregulation of immune inhibitory molecules. Biopsies without detectable parasite transcripts showed decreased evidence for B cell activation, but increased expression of antimicrobial genes and genes encoding skin barrier functions. The composition and abundance of L. braziliensis transcripts in PTPos lesions were surprisingly conserved among all six patients, with minimal meaningful differences between lesions from patients with early and late cutaneous leishmaniasis. The most abundant parasite transcripts expressed in lesions were distinct from transcripts expressed in vitro in human macrophage cultures infected with L. amazonensis or L. major. Therefore in vitro gene expression in macrophage monolayers may not be a strong predictor of gene expression in lesions. Some of the most highly expressed in vivo transcripts encoded amastin-like proteins, hypothetical genes, putative parasite virulence factors, as well as histones and tubulin. In summary, RNA sequencing allowed us to simultaneously analyze human and L. braziliensis transcriptomes in lesions of infected patients, and identify unexpected differences in host immune responses which correlated with active transcription of parasite genes.